2017
DOI: 10.1111/ijd.13507
|View full text |Cite
|
Sign up to set email alerts
|

Management of radiodermatitis associated with cetuximab in squamous cell carcinomas of the head and neck

Abstract: The objective of this review is to report to the medical community the most recent knowledge on prevention and management of dermatitis with the use of cetuximab simultaneously with radiotherapy in the treatment of squamous cell carcinomas of the head and neck. A review was conducted in PubMed of English language publications between 2010 and 2015. The search employed the terms 'skin toxicity', 'radiodermatitis', 'cetuximab', 'radiotherapy', and 'head and neck cancer'. Data related to the classification and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The development and severity of acute RD depends on multiple factors intrinsic and extrinsic to the person, including age, sex, diabetes, smoking, tumor site, current treatment, treatment technique, total dose, and fractioned dose. 1,5,23 In this pilot study, the 2 groups evaluated (chamomile gel and urea cream) were balanced on all extrinsic and intrinsic factors that we measured and that could contribute to differences in susceptibility to RD. Therefore, we expect that those factors were not the source of the differences we observed in the figures.…”
Section: Discussionmentioning
confidence: 99%
“…The development and severity of acute RD depends on multiple factors intrinsic and extrinsic to the person, including age, sex, diabetes, smoking, tumor site, current treatment, treatment technique, total dose, and fractioned dose. 1,5,23 In this pilot study, the 2 groups evaluated (chamomile gel and urea cream) were balanced on all extrinsic and intrinsic factors that we measured and that could contribute to differences in susceptibility to RD. Therefore, we expect that those factors were not the source of the differences we observed in the figures.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab is a recombinant human‐mouse chimeric EGFR monoclonal antibody used in the treatment of squamous cell carcinoma of the head and neck and in metastatic bowel cancer . During its clinical trials in 2007, O'Neil et al .…”
Section: Immediate Anaphylaxis: Cetuximabmentioning
confidence: 99%
“…Cetuximab is a recombinant human-mouse chimeric EGFR monoclonal antibody used in the treatment of squamous cell carcinoma of the head and neck and in metastatic bowel cancer. 19,20 During its clinical trials in 2007, O'Neil et al 21 reported an increased incidence (22%) of grade 3 or 4 hypersensitivity reactions during or after first infusion in certain American states as compared to the international average of ≤3%. These same patients also reported having episodes of delayed anaphylaxis after ingesting mammalian meat.…”
Section: Immediate Anaphylaxis: Cetuximabmentioning
confidence: 99%
“…With regard to the time from RT, early effects are visible during or immediately after RT and may last for 2‐3 weeks following completion of treatment. These include oral mucositis, pain in teeth and gingiva, taste loss, trismus (due to pain), odynophagia, dysphagia, candidosis, radiation dermatitis (RD), and osteoradionecrosis (ORN) 9,10 . Acute issues usually resolve with time, professional guidance, and medication.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple topical medications and nonpharmacologic agents have been tried in the prevention and treatment of RD but there is no strong evidence to indicate preference between either group of the topical agents 10,105 …”
Section: Introductionmentioning
confidence: 99%